Cynara cardunculus L. as a Multipurpose Crop for Plant Secondary Metabolites Production in Marginal Stressed Lands - Pappalardo, Helena Domenica; Toscano, Valeria; Puglia, Giuseppe Diego; Genovese, Claudia; Raccuia, Salvatore Antonino (Frontiers in Plant Science, 2020)
Cardoon (Cynara cardunculus L.) is a perennial crop of the Asteraceae family, native to the Mediterranean region, characterized by high production of biomass and secondary metabolites, usable for green chemistry and in the nutraceutical and pharmacological sectors. Recent studies demonstrated the ability of cardoon to grow up in a stressful environment which is associated with enhanced biosynthesis of biologically active compounds in these plants and this effect is increased by abiotic stresses (salt, heat, pollution and drought stress) that characterize many world marginal areas, affected by the climate changes. The plant response to these stresses consists in implementing different processes that modify some plant biological functions, such as alleviating both cellular hyperosmolarity and ion disequilibrium or synthesizing antioxidant compounds. The aim of this work was to investigate different cardoon response mechanisms to abiotic stresses and to evaluate their influence on the biologically active compounds biosynthesis. Following this purpose, we analysed the ability of cardoon seeds to germinate under different salt stress conditions and on the sprouts obtained, we measured the Total Phenols Content and the Antioxidant Activity. Moreover, the growth of cardoon seedlings grown under heavy metals stress conditions was monitored and the expression levels of heavy metal transport associated genes was analysed. The results showed the ability of cardoon plants to tolerate abiotic stress thanks to different defence mechanisms and the possibility to obtain biomass with high content of biologically active molecules by exploiting the natural tolerance of this species for abiotic stresses. Moreover, we identified some important genes encoding for metal transportation that may be involved in the uptake and translocation of As and Cd in C. cardunculus. Then, this species can be considered as a promising crop for green chemistry and energy in marginal lands.